2019
DOI: 10.1111/add.14547
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and correlates of polysubstance use among US youth aged 15–17 years: wave 1 of the Population Assessment of Tobacco and Health (PATH) Study

Abstract: Background and Aims: Youth aged 15-17 years are at high risk of tobacco, alcohol, and drug use. Given the changing landscape with respect to availability, use of emerging products, and regulatory environments, we examined patterns and correlates of poly-substance use among U.S. youth aged 15-17 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
6
21
0
5
Order By: Relevance
“…Regarding Polysubstance Users, it is important to note that adolescents within this class tended to make combined use of three specific substances, alcoholtobacco-marijuana, at a significantly higher frequency than the three previous groups, which points to a more problematic pattern of use, characterizing 23% of the sample. Classes with a similar pattern of use were also identified in previous studies (Silveira et al 2019;Tomczyk et al 2016). A significantly higher involvement in violence, as an aggressor or a victim, was associated with this pattern of use, in comparison with Abstainers, Drinkers and Conventional Users.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding Polysubstance Users, it is important to note that adolescents within this class tended to make combined use of three specific substances, alcoholtobacco-marijuana, at a significantly higher frequency than the three previous groups, which points to a more problematic pattern of use, characterizing 23% of the sample. Classes with a similar pattern of use were also identified in previous studies (Silveira et al 2019;Tomczyk et al 2016). A significantly higher involvement in violence, as an aggressor or a victim, was associated with this pattern of use, in comparison with Abstainers, Drinkers and Conventional Users.…”
Section: Discussionsupporting
confidence: 78%
“…Throughout all four cohorts, adolescents who reported more psychosomatic problems were more likely to be in the alcohol and polysubstance use classes rather than the non/low use class, in line with other LCA studies [21]. We hypothesized that psychosomatic problems would be less strongly associated with patterns of substance use in the earlier cohorts, when substance use was more common, compared to the later cohorts when it was less common.…”
Section: Discussionsupporting
confidence: 68%
“…One LCA study revealed that females were more likely to use different types of substances [9], whereas others found that class probabilities for substance use classes did not differ between males and females [23]. Similarly, some studies found that females were more likely to be included in tobacco and polysubstance use classes [21], but others found that males were more likely to be included in a polysubstance use class or typology [23,34]. Other studies did not observe sex differences [22,25,26].…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…The following thresholds were used to categorize participants for each variable: 0–1 symptoms in the past year (low), 2–3 symptoms in the past year (moderate) and 4+ symptoms in the past year (high). Further details have previously been published out of the PATH Study (Conway et al, 2017; Silveira et al, 2019; Pearson et al, 2017).…”
Section: Methodsmentioning
confidence: 99%